Analysis of Technology Acceptance Model: Case Study of Traveloka - Anam Hadi Nugroho; Abu Bakar; Ahmad Ali (Arthatama: Journal of Business Management and Accounting, 2017)
One of the factors that can influence users’ desire to use technology, especially online applications, is the perception of the usefulness and ease of use of the technology offered. This is a reasonable action in the context of the use of technology, where one will first see the benefits and ease of use of technology. This context makes the behavior of the person a benchmark for accepting technology. This study seeks to explain the application of Technology Acceptance Model theory by one of the largest travel companies in Indonesia, Traveloka, which connects the psychological aspects of users to obtain convenience in the use of technological application of Traveloka. This study used the case study supported with extensive literature review in terms of online platform development and of the theory of Technology Acceptance Model. The results show that perceived ease of use and perceived usefulness are the two most important considerations in the adoption and use of an application by the users. These two considerations have become the inherent concept of Traveloka services, which offer complete online booking features for flights and hotels.